Pengaruh Konsentrasi Pupuk Organik Cair (POC) Terhadap Pertumbuhan Vegetatif Talas (Colocasia esculenta L. Schott) - Purnomo (Indoensia), Astin Panji; Suprapto (Indoensia), Agus; Jannah (Indoensia), Eka Nur (Universitas Tidar, 2023)
Taro (Colocasia esculenta L. Schott) is e tuber commodity that contains carbohydrates and can be used as an alternative source of food besides rice. This research was aimed to get the effects of liquid organic fertilizer on Taro’s vegetative growth. The research was conducted on September - December 2021 at Kebun Pendidikan Pengembangan Pertanian Bandongan Laboratory of Agriculture Faculty, Tidar University, Bandongan, Magelang Regency with an altitude of 360 m asl. The research method was arranged in Completely Randomized Block Design using a non-factorial experiments with one experiment factor and repeated three times. The research factor is POC concentration with levels: 0, 2, 3, and 4 ml/l. The research results show that POC applications with 3-4 ml/l concentration showed a very significant difference in length of stalk and significantly different in plant height.